A New Sufficient Condition for Checking the Robust Stabilization of Uncertain Descriptor Fractional-Order Systems. (18th July 2018) - Wang, Hongxing; Liu, Aijing
Abstract : We consider the robust asymptotical stabilization of uncertain a class of descriptor fractional-order systems. In the state matrix, we require that the parameter uncertainties are time-invariant and norm-bounded. We derive a sufficient condition for the system with the fractional-orderα satisfying1 ≤ α < 2 in terms of linear matrix inequalities (LMIs). The condition of the proposed stability criterion for fractional-order system is easy to be verified. An illustrative example is given to show that our result is effective.